Consulting project in entrepreneurship for a technological platform of care, support and health services on demand - Canales Cavenago, Angela Annette Antoinete (2019)
BWMe (Be with me) is a business idea that aims to provide a reliable, humanized and differentiated service of support, care and health through a technological platform by providing assistance and medical care on-demand, especially for the elderly, people with disabilities or whoever might need assistance in Lima – Peru. The services will be supported by a 24/7 helpline for service providers and costumers. Three types of services will be offered: Care & Support, Support & Health and Prevention & Support. The service providers will have certificated knowledge of first-aid program and Cardiopulmonary resuscitation (CPR - the company could provide training in case applicants do not possess it) or will be certified nurses, nursing assistants or qualified physical therapists depending on the selected service. The free download application will provide a detailed profile of the helpers, their capabilities and the ratings they get from their services, so customers can choose the partner they want and who could fit better with their needs. The application will calculate fees according to the hours of service, type of service and time of service, providing a quotation and different payment methods. Its value proposal is the convenience, reliability and accessibility that these services will bring.